AiREAS: Sustainocracy for a Healthy City Phase 3: Civilian Participation - Including the Global Health Deal Proposition - Close, Jean-Paul (SpringerBriefs on Case Studies of Sustainable Development,, 2016)
This volume describes phase 3 of the AiREAS multidisciplinary cocreation effort to produce a Healthy City. Phase 1 referred to making visible the invisible from an air quality and human exposure perspective. Phase 2 studies air quality related to health and Phase 3 looks at air quality, health and lifestyle from the perspective of persuasion to innovative change. The three books together describe the coming about and first results of the AiREAS "healthy city" cooperative in the city of Eindhoven and Province of North Brabant in the Netherlands. AiREAS is an initiative focused on the multidisciplinary co-creation of healthy cities using the core human value of human health and air quality as guiding principle for profound regional innovation.